The effect of size on the magnitude of long‐window earnings response coefficients* - CHANEY, PAUL K.; JETER, DEBRA C. (Contemporary Accounting Research, 1992)
Abstract. This paper reports the results of an empirical investigation of the effect of firm size on the magnitude of the long‐window earnings response coefficient (ERC). In contrast to earlier studies, we find that size is positively related to the magnitude of the long‐window ERC. This result was robust across alternative event windows (12, 15, and 24‐months). The argument advanced in the literature has been that since more information is available throughout the year for large firms, a less pronounced market reaction occurs at the earnings announcement date. Our result is not inconsistent with this since we examined the relationship over a long window. It appears that the greater availability of alternative information sources and increased search activities about large firms, rather than resulting in a weaker ERC for large firms, may actually enhance or strengthen the magnitude of the long‐window ERC. Our intepretation of this finding is that the broader set of information available about large firms enables market participants to interpret the information in the financial statements more completely and to estimate future cash flows more accurately, leading to a decreased level of system uncertainty. In addition, we present evidence that the largest response coefficients are for large nonsurvivor firms while the smallest are for small firms, both survivors and nonsurvivors. Résumé. Les auteurs rapportent les résultats d'une analyse empirique de l'incidence de la taille de l'entreprise sur l'amplitude du coefficient de réponse des bénéfices (CRB) à longue échéance. Contrairement aux études précédentes, celle‐ci débouche sur la conclusion que la taille est en relation positive avec l'amplitude du CRB à longue échéance. Ce résultat persiste, quelle que soit la période d'événements choisie (12, 15 ou 24 mois). L'explication proposée dans les travaux précédents est la suivante: puisqu'il est possible d'obtenir davantage d'information tout au long de l'année au sujet d'une grande entreprise, la réaction du marche est moins prononcée à la date de la déclaration des bénéfices. Les résultats de l'étude ne sont pas contradictoires puisque les auteurs étudient la relation à longue échéance. II semble que l'eventail plus grand du choix de sources d'information et les activités de recherche plus importantes en ce qui a trait aux grandes entreprises, plutôt que de donner lieu à un CRB plus faible dans leur cas, puissent en fait favoriser ou renforcer l'amplitude du CRB à longue échéance. Les auteurs en déduisent que le réservoir d'information plus large dont on dispose au sujet des grandes entreprises permet aux intervenants sur le marché d'interpréter les renseignements fournis dans les états financiers de façon plus complète et de mieux estimer les flux monétaires éventuels, ce qui conduit à une réduction de l'incertitude relative au système. De plus, les auteurs démontrent que les coefficients de réponse les plus élevés sont ceux des grandes entreprises qui ne survivent pas, tandis que les coefficients de réponse les plus faibles sont ceux des entreprises plus petites, qu'elles survivent ou non.